Development of arc welding technique to preclude microsegregation in the dissimilar joint of Alloy C-2000 and C-276. (October 2021) - Arulmurugan, B; Sathishkumar, M; Balaji, D; Muralikrishnan, K; Pranesh, S; Praveen, V; Praveen Kumar, K; Arivazhagan, N; Manikandan, M
Hastelloy C-2000 and C-276 are widely used in Flue Gas Desulphurization (FGD) system and Chemical Processing Industries (CPI). Current work is focused on weld microstructure, and mechanical properties (structure-property relationship) of the dissimilar combination of alloy C-2000 and C-276. Multi-pass Pulsed Current Gas Tungsten Arc (PCGTA) welding was adopted for joining the dissimilar alloys using the filler ERNiCrMo-17. Microstructural characteristics of the weld joint were assessed by Optical and Scanning Electron Microscope (SEM). Weld interface microstructure examination revealed the presence of grain coarsening near the Heat Affecting Zone (HAZ) of the alloy C-276 side. SEM analysis shows the absence of secondary Topologically Closed Packed (TCP) phases in the Inter-Dendritic (ID) regions of the dissimilar weld. Micro-segregation of alloying elements in the weldment was assessed by Energy-Dispersive X-ray Spectroscopy (EDS). X-Ray Diffraction (XRD) analysis had been carried out to identify the phase constitution and average grain size. Strength, toughness, and hardness of the dissimilar weld were evaluated with the support of the tensile test, Charpy impact test, and Vicker's hardness test. Tensile study showed that all the tensile fracture occurred at the base metal side of alloy C-276. The average toughness of the dissimilar alloy joint was noted about 84 J. Hardness test results indicated that fusion zone (FZ) hardness value was 6.19% and 2.27% superior to the candidates' material (C-276 and C-2000) employed in this study. The refined grain structure and absence of microsegregation resulted in the highest hardness in the dissimilar weld FZ. Results revealed the substantiated use of PCGTA welding for the effective joining of dissimilar alloys of C-2000 and C-276 through the evaluation of metallurgical and mechanical characteristics.